THE BEST EVIDENCE FOR JEWISH SERVICE IN THE ROMAN ARMY: A NEW LOOK AT THE JEWISH EXEMPTIONS FROM MILITARY SERVICE AS APPEARING IN JOSEPHUS, AND JEWISH MILITARY SERVICE IN THE LATE REPUBLIC AND EARLY PRINCIPATE - Haggai OLSHANETSKY (Journal of Ancient History and Archaeology)
This article aims to re-examine the exemptions from military service that were given to the Jews in the Late Republic, conserved to us in Josephus' writings. The extent of these exemptions and their number are part of a long, extensive scholarly debate. This article wishes to prove that there were only two original exemptions, one issued by Lentulus and one by Julius Caesar, that were limited in their extent, and that there was never a general exemption for all the Jews. It will also be shown that the other exemptions are only edicts renewing the previous two. Moreover, it will be proven that the Jews served no less than their percentage in the general population, and that extensive Jewish service started in the middle of the 1st century BCE. By showing this and highlighting the vast number of Jews that were in the domain of the Roman Republic at the time, especially in the city of Rome, the current article will stress that there was no logical reason to give a general exemption to the Jews in a time of war. And so, an attempt to delve into the logic behind the exemptions, their extent, and the reason for their creation, will be made. Another aspect which will be addressed is the role of the local Roman administration in issuing edicts, their extensive understanding of the different minorities, including the Jews, and the legislative tradition of not creating precedence.